Adjuvant chemotherapy compared with observation in patients with T2aN0 stage IB lung adenocarcinoma - Lee, Po-Hsin; Chiang, Chun-Ju; Tseng, Jeng-Sen; Zheng, Zhe-Rong; Chen, Kun-Chieh; Chu, Cheng-Hsiang; Huang, Yen-Hsiang; Hsu, Kuo-Hsuan; Lee, Wen-Chung; Yang, Tsung-Ying; Liu, Tsang-Wu; Hsia, Jiun-Yi; et al. (Frontiers in Oncology, 2023)
Background: For patients with T2aN0 stage IB lung adenocarcinoma, benefits of adjuvant chemotherapy remain controversial. Here, we aimed to evaluate such benefits. Methods: This retrospective cohort study was conducted on the database of the National Taiwan Cancer Registry. We analyzed patients with T2aN0 stage IB lung adenocarcinoma (re-classified by AJCC 8th edition) diagnosed during the period from January 2011 to December 2017. They were divided into two groups: (1) group 1: tumor <=3 cm with visceral pleural invasion (VPI); (2) group 2: tumor >3 cm, but <=4 cm. Overall survival (OS) and cancer specific survival (CSS) were evaluated. Risk factors for survival were determined. Results: A total of 2,100 patients with T2aN0 stage IB lung adenocarcinoma (1,265 in group 1 and 835 in group 2) were enrolled for study. The proportions of patients receiving adjuvant chemotherapy in group 1 and 2 were 39.1% and 68.6%, respectively. Amongst group 1 patients, adjuvant chemotherapy was not an independent risk factor for OS and CSS. Amongst group 2 patients, high-grade histologic findings and receiving sublobar resection were two risk factors for poorer survival. Adjuvant chemotherapy was also associated with an OS (adjusted hazard ratio (aHR), 0.52; 95% confidence interval (CI), 0.38-0.72; P<0.001) and CSS (aHR, 0.54; 95% CI, 0.37-0.78; p=0.001) benefit regardless of the presence or absence of risk factors. Conclusion: For patients with T2aN0 stage IB lung adenocarcinoma, adjuvant chemotherapy improved OS and CSS in those with tumors >3 cm, but <=4 cm. For patients with tumors <=3 cm with VPI, adjuvant chemotherapy had no survival benefit.